Assessment of Using Cement Kiln Dust Stabilized Roads Subbase Material - Abdulzahra Mahdi, Zaid; Abbas Hasan, Mohammed; Ahmad Jasim, Heydar (International Journal of Engineering and Technology, 2018)
The increase in the demand for cement to produce large quantities for the purpose of reconstruction produce a large amount of cement kilns dust accordingly. The cement kilns has a cementations property and it’s using to treats soil. In this study, sand gravel soil (roads subbase) materials has been used to study the effect of the cement kiln dust (CKD) as a partial replacement with the natural dust of subbase till 20% by weight. Three tests procedures have been adopted which are density-moisture relationship, California bearing ratio (CBR), and unconfined compression strength (UCS). The results show significant increasing in density and optimum moisture content, CBR, and UCS with the increasing of CKD content. Bonds induced by the pozzolanic reaction and the absorption of the free water on particles surfaces approaching each other could the cause of increasing density, forming tighten structure, and raising the CBR% values, this reaction needs more water with increasing of CKD that could be caused increasing in the optimum moisture content. The increasing in UCS results due to stabilizing the materials by CKD increased the ability to use the CKD as alternative material for Portland cement. Â